2014
DOI: 10.1159/000360449
|View full text |Cite
|
Sign up to set email alerts
|

27-Gauge Vitrectomy

Abstract: Ten years or more have passed since the current concept of 25-gauge transconjunctival sutureless vitrectomy with a trocar-cannula system emerged. There is no doubt that current microincision vitrectomy surgery with 25- or 23-gauge instrumentation has simplified the vitrectomy procedure and has provided numerous potential advantages over traditional 20-gauge surgery. The established theory regarding surgical wounds is that 'much smaller is better'. Along with the development of new-generation vitrectomy machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…Smaller vitrectomy probes allowed the transition to the microincision vitrectomy system (MIVS), introduced in 2002 by Fujii et al, using 25-gauge instruments and followed by Eckardt in 2005, with 23-gauge cutters [46]. Subsequent years have shown that the modern MIVS have numerous advantages over 20-gauge vitrectomy and are associated with better patient comfort, less conjunctival scarring, less postoperative inflammation and earlier visual recovery [711]. More recently, 27-gauge instruments released by different companies have shown encouraging results [79, 12, 13].…”
Section: Vitrectomy Cuttersmentioning
confidence: 99%
See 3 more Smart Citations
“…Smaller vitrectomy probes allowed the transition to the microincision vitrectomy system (MIVS), introduced in 2002 by Fujii et al, using 25-gauge instruments and followed by Eckardt in 2005, with 23-gauge cutters [46]. Subsequent years have shown that the modern MIVS have numerous advantages over 20-gauge vitrectomy and are associated with better patient comfort, less conjunctival scarring, less postoperative inflammation and earlier visual recovery [711]. More recently, 27-gauge instruments released by different companies have shown encouraging results [79, 12, 13].…”
Section: Vitrectomy Cuttersmentioning
confidence: 99%
“…Subsequent years have shown that the modern MIVS have numerous advantages over 20-gauge vitrectomy and are associated with better patient comfort, less conjunctival scarring, less postoperative inflammation and earlier visual recovery [711]. More recently, 27-gauge instruments released by different companies have shown encouraging results [79, 12, 13]. …”
Section: Vitrectomy Cuttersmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we should take heed to our anterior segment surgeons and look to minimize the invasiveness of vitrectomy for floaters. Recently, I have begun using 27-gauge vitrectomy for floater removal in order to eliminate the need for a local block and postoperative eye patch [23,24]. The early results and patient feedback have been encouraging, as patients have started enjoying the visual benefits in the recovery room.…”
Section: Resultsmentioning
confidence: 99%